A special issue of Phytotaxa dedicated to Bryophytes: The closest living relatives of early land plants - Von Konrat, M.; Shaw, A. J.; Renzaglia, K. S. (Phytotaxa, 2014)
This special volume is dedicated to Bryophytes. It includes an editorial plus 13 chapters. All papers are for open access.